2019
DOI: 10.3390/w11020285
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Land Use and Climate Change on the Water Yield of a Watershed in Colombia

Abstract: Land use and climate are two determinant factors of water yield within a watershed. Understanding the effects of these two variables is key for the decision-making process within watersheds. Hydrologic modeling can be used for this purpose and the integration of future climate scenarios to calibrated models widens the spectrum of analysis. Such types of studies have been carried out in many areas of the world, including the Amazon Basin of South America. However, there is a lack of understanding on the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Remote sensing data from Australia's Murray-Darling basin found significant regional variability in water retention, with climate change accounting for 70% of the variability [18]. The combined effects of climate and land-use change also were assessed using SWAT in a small Columbian watershed of less than 200 km 2 [19]; the results indicated that climate and land-use change determine water yield within this watershed. A similar study in a small West African watershed discovered that land cover amplified climate change impacts on water retention [20].…”
Section: Regional Variabilitymentioning
confidence: 98%
See 1 more Smart Citation
“…Remote sensing data from Australia's Murray-Darling basin found significant regional variability in water retention, with climate change accounting for 70% of the variability [18]. The combined effects of climate and land-use change also were assessed using SWAT in a small Columbian watershed of less than 200 km 2 [19]; the results indicated that climate and land-use change determine water yield within this watershed. A similar study in a small West African watershed discovered that land cover amplified climate change impacts on water retention [20].…”
Section: Regional Variabilitymentioning
confidence: 98%
“…Distinguishing between the impacts of climate and land cover on water retention is particularly important for adaptive management [17]. Research in this discipline has been carried out in numerous watersheds around the globe, including the analysis of effects of climate and land-use on surface water extent dynamics in Australia's Murray-Darling Basin [18], on the water yield of the Tona watershed [19], on water resources and soil erosion in the Dano catchment in south-western Burkina Faso [20], on the water resources in the eastern Baltic Sea [21], on the combined impacts of future land-use and climate on water resources and quality of the Thames River basin in the southern UK [22], and the analysis of land-use change may exacerbate the climate change impacts on water resources in the Upper Ganges river basin in northern India [23]. All of these studies assessed the independent or combined effects of climate and land-use impacts, but none assessed their contributions to or regional differences in the impacts on water retention services.…”
Section: Introductionmentioning
confidence: 99%
“…Under severe emissions, the largest variations are projected during 2050s ranging from −62.2% to 30.4%. Winter water yield projections indicate decrease during the mid-century period and slight increase by end of the century under both emissions scenarios [23].…”
Section: Implication Of Future Water Regimementioning
confidence: 97%
“…Consequently, global mean temperature has been rising 1.5 • C above preindustrial (1850-1900) era [1]. Other key indicators of the critical situation are Sea Level Rise (SLR) and Sea Ice Extent (SIC); both are the direct consequence of greenhouse gas (GHG) increase conservation practices [23]. Marhaento et al [24] studied climate and LUC in a tropical watershed in Indonesia and found intensification in annual stream flow and surface runoff if the drivers combined; the LUC scenarios used in the study were based on extrapolation of trends [24].…”
Section: Introductionmentioning
confidence: 99%
“…It has strong applicability in predicting future changes in water resources, and it is convenient to use the spatial information provided by remote sensing technology or computer technology to simulate the hydrological effects in many different scenarios (Shang et al, 2019). Therefore, the SWAT model has been used in many areas, like Minnesota, Michigan, and Colombia of the United States (Schomberg et al, 2005;Villamizar et al, 2019), San Pedro watershed of Mexico (Nie et al, 2011), Amur River Basin of Asia (Zhou et al, 2020), and Ganga River Basin of India (Anand et al, 2018).…”
Section: Introductionmentioning
confidence: 99%